Colchicine for primary prevention of atrial fibrillation after open-heart surgery: Systematic review and meta-analysis. (15th December 2017) - Lennerz, Carsten; Barman, Manish; Tantawy, Mahmoud; Sopher, Mark; Whittaker, Peter
Abstract: Background: Atrial fibrillation occurs frequently after open-heart surgery. It is associated with increased morbidity and mortality, longer hospital stays, and increased healthcare costs. Prophylactic administration of colchicine may mitigate post-operative atrial fibrillation (POAF). Methods: We searched PubMed, ClinicalTrials.gov and CENTRAL databases to identify randomized controlled trials (RCTs) that; (1) compared prophylactic use of colchicine to placebo, or usual care, in patients with sinus rhythm who underwent elective open-heart surgery and (2) reported POAF-incidence. We excluded trials focused on incidence of atrial fibrillation after percutaneous interventions or colchicine treatment of diagnosed pericarditis or post-pericardiotomy-syndrome. A random-effects model was used to pool data for POAF-incidence as the primary outcome and for drug-related adverse effects, major adverse events (death and stroke), and hospital length-of-stay as secondary outcomes. Results: We included five RCTs (1412 patients). Colchicine treatment reduced POAF-events by 30% versus placebo or usual care (18% vs. 27%, risk ratio (RR) 0.69, 95% confidence interval (CI) 0.57 to 0.84, p = 0.0002). Adverse drug-related effects, especially gastrointestinal intolerance, increased with colchicine; (21% vs. 8.2%, RR 2.52, 95% CI 1.62 to 3.93, p < 0.0001). However, major adverse events were unchanged (3.2% vs. 3.2%, RR 0.96, 95% CI 0.48 to 1.95, p = 0.92). Length-of-stay decreased by 1.2 days with colchicine (95% CI -1.89 to − 0.44, p = 0.002). Conclusion: Colchicine demonstrated superior efficacy versus usual care for prevention of atrial fibrillation after cardiac surgery. Moreover, colchicine treatment was associated with shorter hospital stays. These benefits outweigh increased risk of adverse drug-related effects; although further work is needed to minimize gastrointestinal effects.